Aluminum phthalocyanine tetrasulfonate conjugated to surface-modified Iron oxide nanoparticles as a magnetic targeting platform for photodynamic therapy of Ehrlich tumor-bearing mice - Omnia G. Fauiod; Maha Fadel; Ahmed El-Hussein; Doaa Abdel Fadeel (Photodiagnosis and Photodynamic Therapy)
Background: Photodynamic therapy (PDT) is a targeted treatment option for cancers that are non-responding to ordinary anticancer therapies. It involves activating a photosensitizer with a light source of a specific wavelength to destroy targeted cells and their surrounding vasculature. Aluminum phthalocyanine tetra sulfonate (AlPcS4) has gained attention as a second-generation photosensitizer for its strong absorption in the red-light region. AlPcS4 can be conjugated to magnetic iron oxide nanoparticles (IONs) to provide targeted drug delivery to the tumor cells while reducing its undesired effect on healthy tissues in other body parts. Methods: Magnetic glutamine functionalized iron oxide nanocomposites loaded with AlPcS4 (IONs-NH2-AlPcS4) were synthesized via the co-precipitation method. The conjugate (IONs-NH2-AlPcS4) was characterized by TEM, Zeta potential, DLS, FTIR, and UV–VIS absorption spectroscopy. Furthermore, its photodynamic activity was investigated using albino mice with induced Ehrlich solid tumors. Results: AlPcS4 was successfully conjugated to IONs-NH2 with a high loading efficiency of 54±2%. The synthesized conjugate exhibited a spherical shape, with 7 ± 2 nm particle size. The In vivo experiment revealed that the albino mice with induced Ehrlich solid tumor that were treated by combined PDT and magnetic targeting conjugate exhibited significant tumor regression and notably higher levels of necrotic tissue compared to the animals in other groups. Conclusion: PDT mediated by magnetic targeting significantly inhibited tumor growth with minimal adverse effects, indicating its great potential as a promising strategy for solid cancer treatment.